2013
DOI: 10.1002/lsm.22160
|View full text |Cite
|
Sign up to set email alerts
|

Detecting field cancerization using a hyperspectral imaging system

Abstract: The hyperspectral imaging system offers a new, non-invasive method for early detection of field cancerization. Lasers Surg. Med. 45:410-417, 2013. © 2013 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 37 publications
0
36
0
1
Order By: Relevance
“…We have earlier shown that the HIS is useful in the detection of skin field cancerisation (5). In the present study HIS showed its potential in the detection of the subclinical borders of LM and LMM.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We have earlier shown that the HIS is useful in the detection of skin field cancerisation (5). In the present study HIS showed its potential in the detection of the subclinical borders of LM and LMM.…”
Section: Discussionmentioning
confidence: 85%
“…We have earlier shown that a novel hyperspectral imaging system (HIS) efficiently detects areas of subclinical skin field cancerisation (5). Hyperspectral imaging combines traditional spectroscopy and imaging techniques by producing 3 dimensional data cubes, referred as hyperspectral images, where in addition to spatial (x, y location) information, image contains a spectral graph (z intensity) for each pixel (6).…”
mentioning
confidence: 99%
“…The approach based on hyperspectral imaging of pigmented tissue is also not suitable for implementation in a smart phone. Using A more promising approach would be to make use of the spectral information that is outside the visible spectral range (Neittaanmäki-Perttu et al 2013), which would require thermal detector array rather than a CMOS imager in silicon. A more pragmatic approach would be analyse the visible/ near-IR spectrum in more detail, which would require a microspectrometer.…”
Section: Potential Of Microspectrometers In Appsmentioning
confidence: 99%
“…Many other promising medical applications are in the IR. One example is mentioned already is improving melanoma pre-screening by extending the spectral analysis into the IR (Neittaanmäki-Perttu et al 2013). Opening this field of applications in the IR would require a technique for lowcost, CMOS-compatible fabrication of MEMS-based thermal detector arrays, which is one of the future trends in technology development.…”
Section: Beyond Appsmentioning
confidence: 99%
“…Therefore, various microscopic imaging and spectroscopic modalities and macroscopic approaches [15][16][17][18][19][20][21][22][23] are being developed to detect BCCs for diagnosis, as well as for presurgical assessment of the margins [24][25][26][27][28][29][30][31][32][33][34][35] and for providing feedback for guiding therapy. Of all these, reflectance confocal microscopy (RCM) and optical coherence tomography (OCT) appear to be particularly attractive.…”
Section: Introductionmentioning
confidence: 99%